2018
DOI: 10.1007/s42000-018-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress and body composition disorders: implications for health and disease

Abstract: Recent studies have suggested that body composition is key to health and disease. First, fat tissue is a complex, essential, and highly active metabolic and endocrine organ that responds to afferent signals from traditional hormone systems and the central nervous system but also expresses and secretes factors with important endocrine, metabolic, and immune functions. Second, skeletal muscle mass is an important predictor of health in adult life, while severe mass loss has been associated with the frailty of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 103 publications
1
51
1
2
Order By: Relevance
“…Numerous studies have found that prediabetes is strongly associated with increased weight and BMI [24,25]. Other studies report emotional stress and emotional eating, leading to disruptive behaviors that are linked to increased weight, BMI [26,27], abnormal metabolic profiles, and inflammatory body composition phenotypes [3,8,18]. Interestingly, such conclusions cannot be drawn from the demographic, psychometric, and body composition profile of our study sample.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Numerous studies have found that prediabetes is strongly associated with increased weight and BMI [24,25]. Other studies report emotional stress and emotional eating, leading to disruptive behaviors that are linked to increased weight, BMI [26,27], abnormal metabolic profiles, and inflammatory body composition phenotypes [3,8,18]. Interestingly, such conclusions cannot be drawn from the demographic, psychometric, and body composition profile of our study sample.…”
Section: Discussioncontrasting
confidence: 57%
“…Additionally, the subclinical inflammation of obesity that contributes to the derangement of the metabolic equilibrium suggests that the proinflammatory cytokines secreted by the adipocytes hold a potentially important pathogenetic role [7]. The proinflammatory molecules, either produced by the adipocytes or by physical and mental stress, contribute to body composition disorders, with detrimental implications in adult health [8] (Figure 1). Prediabetes is the stage when the diabetic complications begin.…”
Section: Introductionmentioning
confidence: 99%
“…Among which most reactions require water to occur. In the EROS study, in the groups of athletes ∌80% of the water was located intracellularly, which can be considered as an improvement of the water balance for metabolic purposes (107). Conversely, fat mass is inversely correlated with relative and absolute intracellular water, and consequently lower body water.…”
Section: Hydration As a Key Characteristic For Athletesmentioning
confidence: 99%
“…Both forms of stress have the potential to disrupt the nervous, endocrine and immune systems [13,17], yielding additional psychosomatic manifestations such as fear and anxiety [14,18]. Stressful life events are positively associated with short-, medium-and long-term health disorders [19][20][21], and act as catalysts for the exacerbation of anxiety symptoms, potentially leading to the full development of anxiety disorders [9].…”
Section: Introductionmentioning
confidence: 99%